KULTUR KOTIL, HIPOKOTIL, DAN EPIKOTIL TANAMAN BUAH NAGA SECARA IN VITRO - Sukamto, Lazarus Agus (LIPI Press, 2012)
Dragon fruit plant is usually propagated by using seed or stem cutting. Plant propagation by using seed take long time because of slow growth, whereas by using stem cutting could damage mother plant and the resulted plant is limited. Experimental in vitro propagation was carried out by using cotyledon, hypocotyl and epicotyl from seeds grown in vitro. Culture media was modified Murashige and Skoog (MS) formulation that macro and micro-nutrients were subtracted half-full and addition of plant growth regulators (PGR) 6-benzylaminopurine (BA) combined with?-naphthaleneacetic acid (NAA) for cotyledon and hypocotyl, thidiazuron (TDZ) for epicotyl. Cotyledon explants produced the best callus production on media with addition of PGR 3 mg/l BA + 2 mg/l NAA and the best root production on media with addition of 0 mg/l BA + 5 mg/l NAA. Hypocotyl explants produced the best callus production on media with addition of PGR 1 mg/l BA + 4 mg/l NAA or 3 mg/l BA + 2 mg/l NAA and the best root production on control media. Epicotyl explants produced the best callus production on media with addition of PGR 1 mg/l TDZ and the best shoot, shoot height and root production on control media. The highest shoot number production on 0,001 0,01 mg/l TDZ treatment. Epicotyl is the best explant compared to cotyledon and hypocotyl, especially on control in vitro propagation of dragon plant, which could save the expenses without using PGR.